Speculative Price: Economic Welfare and the Idiot of Chance - Stein, Jerome L. (The Review of Economics and Statistics, 1981)
P AUL COOTNER stimulated significant research on the subject of speculative markets in both commodities and equities. His papers (1960, 1964, 1967) were original and provocative. One paper began with the statement: subject matter of this paper is bound to be considered heresy. I can say that without equivocation, because whatever views anyone expresses on this subject are sure to conflict with someone else's deeply held beliefs (1964, p. 231). Most of the papers concerned with the operation of futures markets in commodities test the 'efficiency of the market by examining the stochastic nature of futures prices (which Samuelson refers to as the Idiot of Chance).' In particular, it is asked whether the price of a futures contract is a martingale. Cootner's contention, which runs counter to the tide of academic writings, is that speculative prices are not random walks but are constrained by economically determined barriers (1964, ch. 11). The present paper is in the spirit of Cootner's thinking about the economic and welfare implications of speculative markets. My main conclusions are as follows. (1) The optimality of resource allocation (defined as the sum of consumer and producer surplus) depends upon the accuracy of the forward price, at the time production decisions are made, as a forecast of the subsequent spot price when consumption occurs. The existence or nonexistence of the martingale property of futures prices between these two dates is irrelevant for welfare purposes. (2) Social loss is a multiple of the square of the forecast error between the forward price and the subsequent spot price. Expected social loss is irreducible when the forward price is equal to the mathematical expectation of the subsequent spot price. (3) The longer the period between the production decisions and the subsequent consumption decisions, the greater the bias between the forward price and subsequent spot price. (4) It has been claimed that in an efficient market, the spot price at time t should just depend upon the price at t 1 and not upon earlier prices. It is proved that this situation is neither a necessary nor a sufficient condition for rational expectations. (5) Therefore, there is a tenuous connection between the stochastic nature of speculative price and measures of economic welfare; but there is a direct connection between the forecast errors and economic welfare.